randRange(1, 10) randRange(1, 10) randRange(1, 10) randRange(1, 10) randRange(1, 10)

Simplify the following expression.

 A + (B \times C) 

A+B*C

 = A + (B*C) 

 = A + B*C 

 = A+B*C 

 A + B \times C 

A+B*C

 = A + B*C 

 = A+B*C 

 A \times (B + C) 

A*(B+C)

 = A \times B+C 

 = A*(B+C) 

 A + (\dfrac{B*C}{C}) 

A+B

 = A + (B) 

 = A + B 

 = A+B 

 A + \dfrac{B*C}{C} 

A+B

 = A + B 

 = A+B 

 \dfrac{ (A*(B+C)) }{ B + C } 

A

 = \dfrac{ (A*(B+C)) }{ ((B+C)) } 

 = \dfrac{ (A*(B+C)) }{ B+C } 

 = A 

 \dfrac{ (A*(B-C)) }{ (B - C) } 

A

 = \dfrac{ (A*(B-C)) }{ ((B-C)) } 

 = \dfrac{ (A*(B-C)) }{ B-C } 

 = A 

 (A + (B - C \times D)) \times E 

(A+(B-(C*D)))*E

 = (A + (B - (C*D))) \times E 

 = (A + ((B-(C*D)))) \times E 

 = (A + (B-(C*D))) \times E 

 = ((A+(B-(C*D)))) \times E 

 = (A+(B-(C*D))) \times E 

 = (A+(B-(C*D)))*E 

 A + (B - C \times D) \times E 

A+((B-(C*D))*E)

 = A + (B - (C*D)) \times E 

 = A + ((B-(C*D))) \times E 

 = A + ((B-(C*D))*E) 

 = A+((B-(C*D))*E) 

 A - B \times C + \dfrac{ (D*E) }{ E } 

A-B*C+D

 = A - B \times C + D 

 = A - (B*C) + D 

 = (A-B*C) + D 

 = A-B*C+D 

 A \times B + C \times \dfrac{ (D*E) }{ E } 

(A*B)+(C*D)

 = A \times B + C \times D 

 = (A*B) + C \times D 

 = (A*B) + (C*D) 

 = (A*B)+(C*D) 

 (A + B \times C) - D \times E 

(A+B*C)-(D*E)

 = (A + (B*C)) - D \times E 

 = (A+(B*C)) - D \times E 

 = (A+(B*C)) - (D*E) 

 = (A+B*C)-(D*E)